Professionalism and professional identity in medical students: a cross-sectional mixed-methods analysis of correlation and progression - Farooq, Munawar; Hashim, Muhammad Jawad; Alhosani, Sultan; Alalawi, Amer Mohammed; Alalawi, Omar Mohammed; Qandilo, Khaled Abdullah; Hafeez, Uffaira; Cevik, Arif Alper (Frontiers in Medicine, 2025)
IntroductionProfessionalism is a core competency in undergraduate and graduate medical education. Professional identity is the internalization of a community’s norms, which results in thoughts, feelings, and actions that align with that community. Uncertainty exists regarding the interrelated progression of professionalism and professional identity. We aimed to explore the professionalism and professional identity scores, as well as their internal correlation, among medical students across different stages of their education.MethodsWe conducted a cross-sectional, observational, complementary mixed-methods study among medical students across all curriculum stages. Quantitative data were collected using the Professionalism Assessment Scale (PAS) and the Professional Identity Questionnaire (PIQ). Qualitative data from two open-ended questions explored students’ perspectives on learning and assessing professionalism.ResultsOne hundred and eight medical students completed the study questionnaires. The reliability coefficient (Cronbach’s alpha) was 0.763 for the PAS questionnaire and 0.767 for the PIQ instrument. PIQ scores had low correlation with empathy, PAS, professional relationships, and responsibility (all r values <0.14). Professionalism (PAS, p = 0.024), empathy (p = 0.009), and professional Relationships (p = 0.007) scores were significantly higher among students in pre-clinical compared to those in basic sciences, however, no significant differences were observed in these scores among students in the pre-clinical, early clinical, and late clinical stages. Professional Responsibility (p = 0.60) and Professional Identity (p = 0.57) scores showed no significant change across all stages.ConclusionThe study highlights plateaus in professionalism and professional identity scores, with no significant correlation between PIQ and PAS scores. While prior literature often treats the two as overlapping or sequential frameworks, our findings suggest the need for separate, targeted strategies in curriculum design to advance both professionalism and professional identity.